2006
DOI: 10.1534/genetics.106.056416
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Quantitative Trait Loci Using the Experimental Designs of Recombinant Inbred Populations

Abstract: In the data collection of the QTL experiments using recombinant inbred (RI) populations, when individuals are genotyped for markers in a population, the trait values (phenotypes) can be obtained from the genotyped individuals (from the same population) or from some progeny of the genotyped individuals (from the different populations).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Although the method presented here concerns the F 2:3 design, its principal may be applicable to any type of F x:y design and some similar design (Kao 2006), that is granddaughter design (Weller et al 1990;Bovenhuis and Weller 1994;Mackinnon and Weller 1995;Ron et al 2001), NCIII design (Cockerham and Zeng 1996), with minor modifications (Zhang and Xu 2004). For example, the new method is extended to an F x:y design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the method presented here concerns the F 2:3 design, its principal may be applicable to any type of F x:y design and some similar design (Kao 2006), that is granddaughter design (Weller et al 1990;Bovenhuis and Weller 1994;Mackinnon and Weller 1995;Ron et al 2001), NCIII design (Cockerham and Zeng 1996), with minor modifications (Zhang and Xu 2004). For example, the new method is extended to an F x:y design.…”
Section: Discussionmentioning
confidence: 99%
“…If the heritability of a trait is low, one can take family mean as a unit of phenotypic measurement (Mather and Jinks 1982;Lynch and Walsh 1998;Zhang and Xu 2004). This is an F 2:3 design in plant genetics (Austin and Lee 1996;Cockerham and Zeng 1996;Fisch et al 1996;Jiang and Zeng 1997;Chapman et al 2003;Zhang and Xu 2004;Kao 2006) and daughter or granddaughter design in animal genetics (Weller et al 1990). These designs are frequently used in mapping QTL in both plant and animal kingdom.…”
mentioning
confidence: 99%
“…The component structures allow us to investigate some QTL mapping properties. For example, the additive (dominance) variances are found to increase (decrease) in the RI or IRI population, showing that these populations may facilitate (hinder) the estimation of the additive (dominance) effects (Kao, 2006). Also, the possible confounding problems in QTL estimation may be identified from the covariances between genetic effects (Kao & Zeng, 2002;Kao, 2006).…”
Section: (I) Data Structurementioning
confidence: 99%
“…Quantitative trait loci (QTL) detection has been a key step to provide deeper insight into the genetic mechanism of quantitative traits in many areas of biological researches, including crops, evolution, ecology and genetical genomics studies etc. (Lander and Botstein 1989;Haley and Knott 1992;Jansen 1993;Zeng 1994;Kao et al 1999;Sen and Churchill 2001;Broman 2003;Kao 2006;Lee et al 2014;Wei and Xu 2016). In QTL detection, it is often found that some of the genomic regions are relatively enriched in QTLs as compared to other regions, and that QTLs responsible for correlated traits frequently co-localize in some specific genetic regions (Goffinet and Gerber 2000;Schadt et al 2003;Chardon et al 2004;West et al 2007;Breitling et al 2008;Wu et al 2008;Li et al 2010;Ali et al 2013;Basnet et al 2015).…”
Section: Introductionmentioning
confidence: 99%